2020
DOI: 10.1002/ijgo.13010
|View full text |Cite
|
Sign up to set email alerts
|

The role of midwives in first-trimester abortion care: A 40-year experience in Tunisia

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution IGO License, which permits unrestricted use, distribution and reproduction in any medium, provided the original work is properly cited. In any reproduction of this article there should not be any suggestion that WHO or the article endorse any specific organization or products. The use of the WHO logo is not permitted. This notice should be preserved along with the article's URL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Generally, abortion is done if there's any death or permanent injuries associated with the risk to a pregnant lady. Recent studies have confirmed the significant role of nurses and midwives to handle pre-abortion cases [73,74] . During pre-abortion period, women need a positive environment, and should not feel alone.…”
Section: Abortionmentioning
confidence: 90%
“…Generally, abortion is done if there's any death or permanent injuries associated with the risk to a pregnant lady. Recent studies have confirmed the significant role of nurses and midwives to handle pre-abortion cases [73,74] . During pre-abortion period, women need a positive environment, and should not feel alone.…”
Section: Abortionmentioning
confidence: 90%
“…With the support of Ipas, committee members were hosted by the government of Tunisia-another francophone country in Africa where abortion is legal, available upon request at no charge, and offered largely by midwives across national family planning centers. 23 Committee members were hosted by Tunisia's National Office of Population and Family Planning, visiting facilities across the country and meeting with abortion providers, feminists, and advocates to better understand the history, value, and limitations of the Tunisian model of abortion care. They exchanged on their mutual vision for comprehensive care and considerations for balancing rights, quality, and access.…”
Section: Progressive Comprehensive Standards and Guidelines Based On ...mentioning
confidence: 99%
“…With the mandate to draft national standards and guidelines, an expert committee of government officials, Ministry of Health experts (PNSR), providers (obstetrician/gynecologists, GPs, and midwives), NGO representatives, community advocates, and legal scholars was assembled. With the support of Ipas, committee members were hosted by the government of Tunisia—another francophone country in Africa where abortion is legal, available upon request at no charge, and offered largely by midwives across national family planning centers 23 . Committee members were hosted by Tunisia's National Office of Population and Family Planning, visiting facilities across the country and meeting with abortion providers, feminists, and advocates to better understand the history, value, and limitations of the Tunisian model of abortion care.…”
Section: Key Milestones and Learningsmentioning
confidence: 99%